Successful adaptation of immigrants to Finland : can cultural fusion work? - Ferlatte Kuisma, Rachel (2017)
Immigration numbers in Finland are growing, more than doubling in the past decade, with immigrants arriving from increasingly diverse regions of the world. An attempt should be made to understand what are the factors that lead immigrants to finding happiness, and to mitigate the apparent rise in assimilation and anti-immigrant attitude in Finland.